A Case Report on Diabetic Ketoacidosis in Children - Keerthana Chandrasekar; Diya C; Vignesh Kumar K (Journal of Global Pharma Technology, 2020)
Abstract:Introduction: Diabetic Ketoacidosis (DKA) is a complex metabolic state characterized by hyperglycaemia, ketonemia and acidosis. It oocurs as a complication of diabetes that results in accumulation of ketone bodies and acidosis in large quantities in the blood. It occurs as a result of a complication of Type 1 Diabetes Mellitus (T1DM) and rarely in Type 2 Diabetes Mellitus (T2DM) in children and adult.Presentation of the case: A 10 year old female child had the complaint of polyuria and polydipsia and within 2 weeks her weight has reduced to 10 kg; she also had itching, burning sensation during micturition and history of vomiting 2 episodes. She was diagnosed as T1DM with DKA and was treated with Intravenous Fluids, cefotaxime, ranitidine and insulin. She was re-admitted with complaints of fever, cough, headache and vomiting for which she was managed symptomatically and discharged.Conclusion: DKA is found to be common; hence early diagnosis and proper education and public awareness should be initiated.Key Words: Diabetic Ketoacidosis, Children, Polydipsia, Polyuria, Type 1 Diabetes Mellitus